Stress and stress tolerance in chronic heart failure - Hambrecht, Rainer (Herz, 2002)
Exercise intolerance in patients with chronic heart failure (CHF) shows no correlation to the degree of left ventricular dysfunction. This surprising finding has directed attention to peripheral changes in CHF. During the last years several different peripheral factors as determinants of exercise intolerance have been defined, i.e. abnormalities in ventilation, reduced endothelium-dependent vasodilatation of peripheral conduit and resistance vessels, and altered skeletal muscle metabolism. Skeletal muscle alterations are characterized by a reduced oxidative capacity, a catabolic state with reduced local IGF-I expression and muscle atrophy, chronic inflammation with local expression of the inducible isoform of nitric oxide synthase (iNOS) and an accelerated rate of programmed cell death (apoptosis). Physical exercise training has evolved as an important therapeutic approach to influence these non-cardiac causes of exercise intolerance. After the first studies documenting the effect of aerobic training on the peripheral causes of exercise intolerance in CHF the question was asked: Should we treat the heart or the periphery to improve exercise intolerance in CHF? Today, we have come closer to the answer: It is now clear that these two systems are not mutually exclusive. Exercise training in CHF has been shown to improve skeletal muscle metabolism and function, to avert muscle catabolism, to reduce neurohumoral overactivation, to reverse endothelial dysfunction and to contribute to the prevention of pathologic left ventricular remodeling. After 6 months of regular exercise training oxidative capacity of the working skeletal muscle increases by approximately 40%. Regular exercise training leads to a significant improvement of endothelium-dependent vasodilatory capacity of peripheral resistance vessels, thereby reducting peripheral resistance in particular during exercise. These beneficial training effects result in a small, but significant improvement of stroke volume and reduction in cardiomegaly. Although several questions regarding patient selection, optimal training protocol and training intensity remain unanswered, exercise training can been seen as an established adjunct to pharmacotherapy in CHF. We may soon reach the conclusion that by treating the periphery with exercise programs we are in fact treating the heart, as well. All exercise-induced adaptations converge to increase peak oxygen uptake by up to 2 ml/kg.min. For patients in stable CHF on optimal cardiac medication a combination of in-hospital and home-based aerobic endurance training in combination with local muscle strength training seems most promising. Although exercise training offers no causal treatment of CHF, it has great potentials as an adjunct therapy directed at improving exercise tolerance and expanding the physical limits of CHF patients.